Loss of CDC4/FBXW7 in Gastric Carinoma - A. N. Milne; R. Leguit; W. E. Corver; F. H. M. Morsink; M. Polak; W. W. de Leng; R. Carvalho; G. J. A. Offerhaus (Cellular Oncology)
Background: CDC4/FBXW7, encoding a ubiquitin ligase, maps to 4q32 and has been implicated as a tumor suppressor gene and therapeutic target in many tumor types. Mutations in colonic adenomas, and the frequent losses on 4q described in gastric cancer prompt speculation about the role of CDC4/FBXW7 in gastric carcinogenesis.